1979
DOI: 10.1080/00994480.1979.10748578
|View full text |Cite
|
Sign up to set email alerts
|

A Note towards the Understanding of Lighting Quality

Abstract: It is perhaps to be regretted that the regular arrays of recessed luminaires, the most common way of lighting offices, are the least preferred. Possibly in a windowless environment the lack of any view to give visual variety exaggerated the low ratings of such situations. Possibly the quality of the luminaires (particularly the prismatic 'batwing' which was rated very low) could be improved. Possibly the experimental procedure which did not allow the subject to work for a long time in the same environment made… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 0 publications
3
45
0
1
Order By: Relevance
“…In their first paper, Hawkes, Loe and Rowlands reported that perceptions of 18 lighting configurations for a windowless two-person office could be described along two independent dimensions: brightness and interest (non-uniformity). 49 They were unable to obtain an interpretable result in their multidimensional scaling analysis.…”
Section: Environmental Appraisalmentioning
confidence: 99%
See 1 more Smart Citation
“…In their first paper, Hawkes, Loe and Rowlands reported that perceptions of 18 lighting configurations for a windowless two-person office could be described along two independent dimensions: brightness and interest (non-uniformity). 49 They were unable to obtain an interpretable result in their multidimensional scaling analysis.…”
Section: Environmental Appraisalmentioning
confidence: 99%
“…For some writers, this judgment defines lighting quality. 49,60 Affect is the term used by behavioral scientists to describe emotional responses. In a state of positive affect, one feels pleasant, relaxed, and happy.…”
Section: Affectmentioning
confidence: 99%
“…4 Several studies are available investigating the way people assess lighting directly. Hawkes et al 5 suggest that people categorise lighting using two dimensions -brightness and interest (or non-uniformity). Flynn et al 6 added a third dimension -overhead versus peripheral lighting distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Light also impacts the affective appraisal or perceived atmosphere of a space and has the potential to change the same space from cosy to tense or from lively to detached (Durak et al 2007;Stokkermans et al 2018;Vogels et al 2008). Light affects the appreciation of a space (Flynn et al 1973;Hawkes et al 1979;Houser et al 2002), sometimes even to the point of inducing pleasure and/or arousal in the visitor (Kuijsters et al 2015). At night, light influences perceptions of safety (e.g., Haans and de Kort 2012), as well as perceived restorativeness of and fascination with urban streetscapes (Nikunen and Korpela 2012).…”
Section: Visual Experiencementioning
confidence: 99%